2013
DOI: 10.1186/1477-7819-11-205
|View full text |Cite
|
Sign up to set email alerts
|

Combined large cell neuroendocrine carcinoma with giant cell carcinoma of the lungs: a case report

Abstract: Combined large cell neuroendocrine carcinoma of the lungs (combined LCNEC) with giant cell carcinoma is extremely rare. A 65-year-old man was found to have an abnormal shadow in his left lung field. Computed tomography revealed a solid, round mass measuring 2.8 × 2.2 cm that was located in the left S9. The patient underwent left lower lobectomy and mediastinal lymph node dissection. Histopathological examination revealed an LCNEC, combined with giant cell carcinoma. The patient received by S-1 (TS-1, an oral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Combined large cell neuroendocrine carcinoma of the lungs with giant cell carcinoma is extremely rare, with a high malignant potential. [ 13 ] It has already been reported that malignant small round cell tumors are generally characterized by small, round and relatively undifferentiated cells. [ 14 ] This morphologic class of tumors contains representatives from almost all major categories of neoplasms, including carcinomas, sarcomas, lymphomas and neuroendocrine–neuroectodermal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Combined large cell neuroendocrine carcinoma of the lungs with giant cell carcinoma is extremely rare, with a high malignant potential. [ 13 ] It has already been reported that malignant small round cell tumors are generally characterized by small, round and relatively undifferentiated cells. [ 14 ] This morphologic class of tumors contains representatives from almost all major categories of neoplasms, including carcinomas, sarcomas, lymphomas and neuroendocrine–neuroectodermal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, mere case reports exist in the literature. 6 , 7 Given the lack of any large series of reports, our study represents a good resource for the study of this rare disease.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed form of NET in the lung is rarely discussed, and to the best of our knowledge, mere case reports are available. 6 , 7 In this report, we conducted a retrospective study to analyze the clinical features, occurrence, treatment, and prognosis of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…As 2 O 3 shows polyploid cells and giant cells; whereas, metanil yellow documents no polyploid cells but with variable shaped giant cells suggesting that endoreduplication may not be the cause of giant cell formation. Hayashi et al (2013) opined that giant cells are the outcome of chaotic mitotic activity due to physiological stresses. Furthermore, such cells are not observed in any squash preparation of untreated control.…”
Section: Cytotoxicity Induced By Arsenic Trioxide and Metanil Yellowmentioning
confidence: 99%